Adansonia Digitata L. (Baobab): A Review of Mineral Element Composition and Ethnomedicinal Values - O. O., Adetola; V. B., Simpson; E. P., Chukwudebe; E. A., Owoeye; O. A., Ayanniyi; O. H, Ayeni (Researchparks Publishing, 2023)
Adansonia digitata L. (Malvaceae) is commonly known as a baobab tree native to Africa. Baobab is a multi-purpose tree that offers protection and provides food, clothing, and medicine as well as raw material for many useful items. The fruit pulp, seeds, leaves, flowers, roots, and bark of baobab are edible and they have been studied by scientists for their useful properties. The fruit pulp has very high vitamin C, calcium, phosphorus, carbohydrates, fibers, potassium, proteins, and lipids content, which can be used in seasoning as an appetizer and also make juices. Seeds contain appreciable quantities of phosphorus, magnesium, zinc, sodium, iron, and manganese, whereas they have high levels of calcium and iron. Baobab has numerous biological properties including antimicrobial, anti-malarial, diarrhea, anemia, asthma, antiviral, anti-oxidant, and anti-inflammatory activities amongst others. The review summarizes the information on various aspects of medicinal properties and importantly mineral content of the tree.